2018
DOI: 10.1111/ans.14304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sarcopenia on the outcomes after pancreaticoduodenectomy for distal cholangiocarcinoma

Abstract: Our findings suggested an association between pre-operative sarcopenia and poor long-term oncological outcomes after PD for DCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…CT has a high degree of validity in determining body composition analysis and is the current gold standard for measuring fat and muscle mass . Unlike most previous studies on biliary tract cancer that measured only psoas muscle area, our study measured total skeletal muscle area on L3 vertebral level in assessing muscle quantity and quality. Psoas muscle includes only <10% of total trunk muscles: therefore, measuring only psoas muscle might not represent the whole skeletal muscle mass and failed to predict the clinical outcome of cancer patients in recent studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT has a high degree of validity in determining body composition analysis and is the current gold standard for measuring fat and muscle mass . Unlike most previous studies on biliary tract cancer that measured only psoas muscle area, our study measured total skeletal muscle area on L3 vertebral level in assessing muscle quantity and quality. Psoas muscle includes only <10% of total trunk muscles: therefore, measuring only psoas muscle might not represent the whole skeletal muscle mass and failed to predict the clinical outcome of cancer patients in recent studies .…”
Section: Discussionmentioning
confidence: 99%
“…In case of biliary tract cancer, there have been a few studies analysing the relationship between prognosis and body composition, limited to a specific location of bile duct cancer (i.e. distal, perihilar, or intrahepatic bile ducts) . To date, there are no study analysing the impact of various body compositions on post‐operative long‐term prognosis by integrating whole biliary tract cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of a large cohort of patients with resected periampullary cancer ( 13 ) showed that patients with cholangiocarcinoma had a higher morbidity rate than those with pancreatic head cancer and that apparent biological differences existed between the 2 groups. Few studies have evaluated the risk of morbidity associated with only distal cholangiocarcinoma ( 19 ) and risk factors for postoperative complications after PD in patients with distal cholangiocarcinoma have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been advances in surgical approaches and perioperative care related to colon cancer, major postoperative complications remain an important cause of morbidity and mortality. Several studies conducted in recent years have found sarcopenia to be associated with short-and long-term adverse outcomes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%